Application of hyaluronic acid in the TMJ for patients with temporomandibular disorders (Research, Society and Development, 2022)
The TMJ consists of an axis joint and time joint, which allows a joint movement of joints, which closes on another axis, in other joints, it is a joint of the most complex joints in the body. Temporomandibular disorders (TMD) are abnormalities that comment on the TMJ. A discussion of the patient's definition of the temporomandibular joint can be broad to alleviate and restore the patient's functions. Several lines of treatment have already been suggested in the literature for the treatment of TMDs, however, there is still a gap in the development of these therapeutic protocols. Thus, the objective of this research was to carry out an indirect and bibliographic approach to analyze the applicability and benefits that hyaloronic acid presents in the treatment of TMD. For this, it was a descriptive approach regarding the performance of atm hyalur acid for patients with dysfunction and to investigate how deficiencies in the last works in the application of time. The research was carried out from secondary school, that is, through format works. articles published between 2005 selected on the platforms Google e2 Forammed, Scientific Electronic Library Online and Pub022. By surveying the effects of intra-articular treatment therapy from articulatory effects, the treatments are effective and do not restore the effectiveness of mandibular tempo reduction. It is concluded that the use of hyaluronic acid is of paramount importance in the treatment of patients who complain of TMD problems.